2021
DOI: 10.1002/jmv.27012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype distribution of high‐risk human papillomavirus in 34 420 cases in Yangzhou city, Jiangsu province, China

Abstract: We aimed to study the infection status and distribution of human papillomavirus (HPV) in Yangzhou City to provide precise guidance for the prevention and treatment of cervical cancer in this area. Reproductive tract secretions were collected from patients admitted at Subei People's Hospital over the past 3 years. Fifteen high‐risk HPV (HR‐HPV) genotypes were analyzed by fluorescent polymerase chain reaction. The positive rate of HR‐HPV in 34 420 subjects was 23.56%. There was no significant difference in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(64 reference statements)
1
7
1
Order By: Relevance
“…That China is vast in territory and huge in population, coupled with unbalanced development, and insufficient awareness of prevention and screening in earlier years and nonstandard cervical cancer screening in certain underdeveloped areas resulted in the regional differences in the epidemiology of HPV and cervical cancer. The overall infection rate of hrHPV in different regions of China was 8.8%-25.7% in recent years [4][5][6][19][20][21][22][23][24][25]. Our study showed that the overall infection rate of hrHPV was 20.3%, which was similar to most reviews or researches on the nationwide prevalence of hrHPV infection in China [4][5][6].…”
Section: Discussionsupporting
confidence: 83%
“…That China is vast in territory and huge in population, coupled with unbalanced development, and insufficient awareness of prevention and screening in earlier years and nonstandard cervical cancer screening in certain underdeveloped areas resulted in the regional differences in the epidemiology of HPV and cervical cancer. The overall infection rate of hrHPV in different regions of China was 8.8%-25.7% in recent years [4][5][6][19][20][21][22][23][24][25]. Our study showed that the overall infection rate of hrHPV was 20.3%, which was similar to most reviews or researches on the nationwide prevalence of hrHPV infection in China [4][5][6].…”
Section: Discussionsupporting
confidence: 83%
“…The HR-HPV infection rate is also different in various regions of China. Our frequency of HR-HPV infection (15.33%) is lower than that previously reported in Fujian (18.68%) [ 20 ], Yangzhou (23.56%) [ 21 ], and Guangzhou (21.12%) [ 7 ], higher than that previously reported in Sichuan (12.6%) [ 22 ], Xinjiang (9.72%) [ 9 ], and Beijing (7.0%), and similar to that reported in Shanghai (15.56%) [ 8 ].…”
Section: Discussioncontrasting
confidence: 81%
“…In our study, the most common genotype was HPV-52, followed by HPV-16, -58, -53 and -39, which was consistent with the result in Guizhou [ 41 ]. HPV-52, -58, -16, -51 and -39 were the five most common HR-HPV genotypes in Yangzhou [ 42 ], and HPV-52, -16, -58, -39 and -51 in Wuhan [ 43 ]. It has been reported that HPV-52 and -58 were the more prevalent genotypes in Asia, especially in China, and infection with them may have association with the cervical cancer development [ 38 , 44 ].…”
Section: Discussionmentioning
confidence: 99%